Analysis of selected elements of knowledge management in the context of the size of the enterprise and the specifics of its activity = Analiza wybranych elementów systemów zarządzania wiedzą w kontekście wielkości przedsiębiorstwa i specyfiki jego działalności - Prusak, Rafał (Zielona Góra: Faculty of Economics and Management Press)
Proper, effective knowledge management is possible only through the implementation of mechanisms and systems tailored to the specifics of the company?s operations and the nature and quantity of its resources. Drawing from the experience of others is advisable, however, to some extent difficult due to the specific uniqueness of many elements of knowledge management in enterprises resulting, for example, from the size of the organization.
Keywords: wiedza; zarządzanie wiedzą; wielkość przedsiębiorstwa; specyfika działalności; knowledge; knowledge management; size of enterprises; activity specifics